Removal of organic dyes from aqueous solution using waste catalyst-derived adsorbent: Isotherm modeling and kinetic studies. (22nd June 2018) - Cheng, Song; Liu, Jian; Hu, Wenhai; Liu, Chao; Zhang, Libo; Xia, Hongying; Peng, Jinhui; Lin, Guo; Jiang, Xin
Abstract: Waste catalyst-derived adsorbent (WCDA) was prepared from the Mercury-containing waste catalyst (MCWC) that was obtained from PVC production process by the method of the microwave–assisted CO2 activation, to remove methylene blue (MB) and methyl orange (MO) from the aqueous solution, achieving the utilization of waste hazardous resources. The optimal experiment condition of the preparation process was performed at 900 °C for 80 min with the CO2 flow rate of 500 ml min −1, with the good performance. The phy-chemical properties of WCDA and MCWC were investigated by N2 adsorption, SEM, FTIR, Raman spectroscopy measurements and x-rayphotoelectronspectra. The WCDA is tested with MB and MO adsorption to assess its potential to liquid phase adsorption. The equilibrium adsorption data showed that the adsorption behavior followed the Langmuir isotherm. The result indicates that the WCDA can adsorb MO easier than MB. The kinetics experiments show that pseudo-second order model matches well the kinetic data. And the adsorption rate of the MO is larger than that of the MB. The above-mentioned analyses indicate that the preparation method of the WCDA is feasible and the WCDA can be as the promising adsorbent for MB and MO removal from aqueous solution.